2020
DOI: 10.1177/1365480220958498
|View full text |Cite
|
Sign up to set email alerts
|

Optimising leadership: Conceptualising cognitive constraints of sociality and collaboration in Australian secondary schools

Abstract: School improvement frameworks and their associated reform efforts often have limited durability and are frequently not fully implemented. Improving their viability, requires a more realistic understanding of contextual organisational structures and the school culture in which the reform is to be implemented. Internationally, and in Australia specifically, education research has informed policy heavily promoting collaboration as a school improvement strategy, with the aim of building teacher capability and stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…The second question led us to investigate what kind of socio-pedagogic educational activities should be supported and developed when designing new ILEs. Supporting earlier findings on the importance enhancing collaboration in schools (Casey et al, 2021 ; DuFour & Mattos, 2013 ), our results indicated that it is critical to design ILEs to strengthen collaborative practices around cross-curricular and cross-organizational activities. The findings also echo the new national curriculum’s recommendation of teacher collaboration (EDUFI, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The second question led us to investigate what kind of socio-pedagogic educational activities should be supported and developed when designing new ILEs. Supporting earlier findings on the importance enhancing collaboration in schools (Casey et al, 2021 ; DuFour & Mattos, 2013 ), our results indicated that it is critical to design ILEs to strengthen collaborative practices around cross-curricular and cross-organizational activities. The findings also echo the new national curriculum’s recommendation of teacher collaboration (EDUFI, 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…Whereas political and educational rules, programs, and procedures, such as legislation and the national curriculum, direct structural changes, cultural change in an organization requires altering prevailing practices, habits, and assumptions (DuFour & Fullan, 2013 ). Hence, fostering a collaborative culture is recognized as a promising strategy for advancing teaching and learning and fostering school improvements (Casey et al, 2021 ; DuFour & Mattos, 2013 ). However, teachers’ collaboration culture varies between school communities and teachers’ informal subgroups (Meredith et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%